Luaran Transfer Embrio Simpan Beku pada Pasien Endometriosis Pasca Operasi dan Non Endometriosis yang Menjalani IVF di Klinik Permata Hati RSUP Dr. Sardjito - Fatmawati, Rina; Widad, Shofwal; Dewanto, Agung (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: Endometriosis is a chronic condition that is influenced by the hormone estrogen which affects women of childbearing age, and is associated with pelvic pain and infertility. In Vitro Fertilization (IVF) is currently the most efficient assisted reproductive technology and its high success rate is often done for infertility therapy in women associated with endometriosisObjective: The aim of this study is to determine whether postoperative endometriosis affected pregnancy outcomes in patients underwent frozen embryo transfer in IVF / ICSI programs.Method: This Research is done with a retrospective cohort design. The data was taken from medical records, research subjects who met the inclusion and exclusion criteria. The research data was collected, processed and analyzed using SPSS 23. Univariate, bivariate and multivariate data analysis was carried out to determine the effect between variablesResult: There were 458 research subjects in this study. Endometriosis patients were 119 subjects (26%). 57 subjects were categorized as minimum-mild endometriosis (47.9%) and moderate-severe subjects as many as 62 subjects (52.1%). The biochemical pregnancy rate (36.31%) and clinical pregnancy (29.4%) in patients with endometriosis was slightly higher than in non-endometriosis. But statistically it did not affect success rate of achieving biochemical (p = 0.428; RR 0.89; 95% CI: 0.71-1.24) and clinical pregnancy (p = 0.535; RR 0.883; 95% CI: 0.63- 1.22). The rate of miscarriage in postoperative endometriosis patients was higher than non-endometriosis patients (88.6% vs 80.7%) but was not statistically significant (p = 0.294; RR 1.69; 95% CI: 0.61-4.67) . Biochemical and clinical pregnancies were significantly affected by age, infertility, endometrial thickness, embryo age and embryo quality. The incidence of miscarriage was affected by the ovarian stimulation protocol.Conclusion: Endometriosis post operative statistically has no effect on pregnancy outcomes in the IVF / ICSI cycle with frozen embryo transfer compared with another cause of infertility .Keywords:Endometriosis, In Vitro Fertilization, Clinical pregnancy, biochemical pregnancy, miscarriage